2019
DOI: 10.1097/phm.0000000000001173
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial on Comparison of the Efficacy of Extracorporeal Shock Wave Therapy and Dry Needling in Myofascial Trigger Points

Abstract: Objective The aim of the study was to compare the efficacy of radial extracorporeal shock wave therapy and dry needling in the treatment of myofascial trigger points in the upper trapezius muscle. Design A total of 65 patients with myofascial trigger points were randomly divided into extracorporeal shock wave therapy group (n = 32) and dry needling group (n = 33). Patients received 3 wks of treatment at 1-wk intervals (in both groups). Visual analog sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 29 publications
6
47
0
1
Order By: Relevance
“…The rESWT for MTPs of UTM as performed in the present study (three rESWT sessions, one session per week, 2000 rESWs per session with EFD + of 0.10 mJ/mm 2 ) was the least session, similar to some previous studies. 22,28,29,30 resulted in a statistically significant improvement in (i) mean elastic index of UTM, (ii) mean VAS score, (iii) mean pressure pain threshold (PPT), and (iv) mean neck disability index (NDI) at one week and 4 weeks to baseline in the ESWT group, which is in line with previous studies. 22,28,29,30 The intergroup comparison with the 1%lidocaine group revealed statistically significantly better results than the rESWT group at T2 and T3, which was not in line but not statistically significant at T4 at p<0.05, which is in line with a previous study that compared with the dry needle.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The rESWT for MTPs of UTM as performed in the present study (three rESWT sessions, one session per week, 2000 rESWs per session with EFD + of 0.10 mJ/mm 2 ) was the least session, similar to some previous studies. 22,28,29,30 resulted in a statistically significant improvement in (i) mean elastic index of UTM, (ii) mean VAS score, (iii) mean pressure pain threshold (PPT), and (iv) mean neck disability index (NDI) at one week and 4 weeks to baseline in the ESWT group, which is in line with previous studies. 22,28,29,30 The intergroup comparison with the 1%lidocaine group revealed statistically significantly better results than the rESWT group at T2 and T3, which was not in line but not statistically significant at T4 at p<0.05, which is in line with a previous study that compared with the dry needle.…”
Section: Discussionsupporting
confidence: 91%
“…33-36 The reduction in the mean VAS score after rESWT found in the present study is in line with the results of earlier studies on ESWT for MTPs. 21-31 The outcome measures in this study are in line with other studies in PPT 21-23,25,27,29 and NDI. 21,25,26,28,29 There are only one 20 of these studies 21-31 that elastic index was applied to monitor treatment success of ESWT for MTPs.…”
Section: Discussionsupporting
confidence: 89%
“…Three hundred and twenty-four ( n = 324) studies remained after removing duplicates. Two hundred and ninety-five ( n = 295) were excluded after the analysis of titles and/or abstracts, leaving 29 articles for final full-text review [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. One article [ 34 ] was excluded because the comparator was acupuncture intervention and the placebo used laser.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen trials (53%, n = 15/28) reported information about adverse effects, with all of them reporting just minor events, and none reported any serious adverse effects [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 38 , 39 , 40 , 41 , 43 , 45 , 50 ]. Post-needling soreness was the most common adverse event and was reported in 53% (8/15) of the trials [ 27 , 28 , 32 , 38 , 40 , 43 , 45 , 48 ] and resolved spontaneously in 24–48h without further treatment.…”
Section: Resultsmentioning
confidence: 99%
“…There are many approaches have been reported to treat MTrPs such as traditional acupuncture, [57] manipulation or massage, [8] medications, [9,10] dry needle, [1115] and other methods. [1618] Acupuncture has been applied for CLBP worldwide, however, it effect for CLBP caused by LMP has not been determined yet. So, we conducted this review to evaluate the effect of acupuncture for CLBP caused by LMP.…”
Section: Introductionmentioning
confidence: 99%